Globalization and liberalization : effects of international economic relations on poverty (UN New YorkUS, 1996)
Focuses on the main issues and constituent elements of the globalization and liberalization process and their effects on poverty. Looks at divergent and significant trends and experiences at the level of developing country regions and of specific individual countries.
DC